The Relationship Between Nurse Career Development and Job Satisfaction at BIMC Kuta Hospital - Pradiptha, I Dewa Agung Gde Fanji; Putra, Made Mahaguna; Wijana, I Ketut; Gayatri, Galih (Babali Publisher, 2024)
Introduction: Quality of Health Services is the level of Health services provided to individuals and communities in an effort to improve outcomes. Nursing services are an integral part of health services so they can contribute to the quality of service in hospitals. Nurse job satisfaction can influence the nursing services provided, which in turn can influence patient satisfaction both directly and indirectly. Employee dissatisfaction can be influenced by organizations that do not have clear career development for employees, which has an impact on reducing overall effectiveness. The aim of this research is to analyze the relationship between career development and job satisfaction of nurses at BIMC Kuta Hospital. Methods: The research design used in this research is a correlational research design using a cross sectional approach. The type of sampling used nonprobability sampling with a total sampling technique with a sample size of 57 nurses. The data collection instrument uses a questionnaire. The bivariate analysis used in this research was the chi square test. Results: Majority of nurses believe that career development at BIMC Kuta Hospital is good, with 41 nurses (71.9%). The majority of nurses are satisfied with their jobs at BIMC Kuta Hospital, with 36 nurses (63.2%).From the results of the analysis, the value OR = 34,000 is also obtained, meaning that nurses with good career development have a 34 times chance of being satisfied with their work. Conclution: There is a significant relationship between career development and job satisfaction with a p-value of 0.000.